2005
DOI: 10.21432/t2jw2p
|View full text |Cite
|
Sign up to set email alerts
|

A Review of What Instructional Designers Do: Questions Answered and Questions Not Asked

Abstract: The purpose of this literature review was to determine what evidence there is that instructional designers apply ID Models, as well as to establish what other activities and processes they might use in their professional activities. Only ten articles were located that directly pertained to this topic: seven reporting on empirical research and three case descriptions recounting development experiences. All ten papers pertained to process-based ID models. Results showed that, while instructional designers appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 16 publications
1
49
0
Order By: Relevance
“…This may signal the possibility of developmental levels -perhaps younger or less experienced designers talk about tasks and technologies rather than larger implications of their work (Schwier, 2004). Recent research examining the actual practice of instructional designers suggests that designers do refer to conventional processes in instructional design but practice varies significantly according to context (Cox, 2003;Cox & Osguthorpe, 2003;Kenny, Zhang, Schwier, & Campbell, 2004;Rowland, 1992;Visscher-Voerman & Gustafson, 2004) and that key aspects of instructional design have been overlooked in conventional literature. Regarding the preparation of instructional designers, critical theorists have described the products and environments graduates produce and deliver as often prescriptive, restrictive, and reductionist, due in no small way to the culture they have acquired within their areas of study and the training that they have received.…”
Section: Conversation As Inquiry: An Alternate Framementioning
confidence: 99%
“…This may signal the possibility of developmental levels -perhaps younger or less experienced designers talk about tasks and technologies rather than larger implications of their work (Schwier, 2004). Recent research examining the actual practice of instructional designers suggests that designers do refer to conventional processes in instructional design but practice varies significantly according to context (Cox, 2003;Cox & Osguthorpe, 2003;Kenny, Zhang, Schwier, & Campbell, 2004;Rowland, 1992;Visscher-Voerman & Gustafson, 2004) and that key aspects of instructional design have been overlooked in conventional literature. Regarding the preparation of instructional designers, critical theorists have described the products and environments graduates produce and deliver as often prescriptive, restrictive, and reductionist, due in no small way to the culture they have acquired within their areas of study and the training that they have received.…”
Section: Conversation As Inquiry: An Alternate Framementioning
confidence: 99%
“…If you are inclined to study this topic in some depth, I recommend Sork's planning model (for a hybrid model I developed, see Figure A1 in Appendix A) and a recent narrative review written by Kenny et al [12]. Furthermore, Jerilyn Veldof, an American academic librarian, has written a book entitled Creating the one-shot library workshop: a step by step guide (see also Veldof's blog) [13].…”
Section: Workhop Design Has Its Own Theorymentioning
confidence: 99%
“…BCA is one of the techniques used to build a business case while a project is being considered by stakeholders, or in its initiating phase (PMI, 2008). In their literature review, Kenny, Zhang, Schwier, and Campbell (2005) found that instructional designers require many non-traditional skills such as communication, editing and proof reading, marketing, media development and graphic design, project management, supervision of personnel, teaching students/faculty development, team building/collaboration, and technology knowledge/programming. Most of these non-traditional instructional design skills and tasks are also identified by the PMI (2008).…”
Section: Disconnect Between Theory and Practicementioning
confidence: 99%